Epidemiological aspects of Helicobacter pylori infection in childhood and adolescence - Kodaira, Marcia S; Escobar, Ana Maria de Ulhôa; Grisi, Sandra (Revista de Saúde Pública, 2002)
The scope of the review is to study the epidemiological aspects of Helicobacter pylori infection and its importance during childhood and adolescence, focusing on incidence, prevalence, transmission and risk factors. The study's references included the following databases: LILACS (PAHO/ Bireme), MEDLINE, the US's National Library of Medicine and the thesis developed at University of São Paulo for the period 1983 to 1999. It was noted that Helicobacter pylori infection is mainly acquired during childhood, age-related prevalence, main risk factors are associated to low socioeconomic status, and its transmission mechanism remains unclear.